Effect of protease supplementation on production performance of laying hens - Filho, Javer Alves Vieira [UNESP] (2015)
The experiment was conducted with the objective of evaluating the effect of protease enzyme supplementation on performance parameters and quality shell of laying hens. We used 240 Isa Brown commercial laying hens with 44 weeks of age. A completely randomized split-plot design (5 periods of 21 days) with four treatments and six replications (10 hens per replication) was used. The experimental diets were formulated according to the requirements of the breed. The following parameters were evaluated: egg production, feed intake, feed conversion, average egg weight, egg loss, specific gravity, percentage and shell thickness. After collection, the data were analyzed with SISVAR Statistical Package, and the means compared by SNK test at 5% probability. It was concluded that supplementation of diets low in nutrients with 500 g ton-1 of protease (100 U g-1), provides egg production and feed conversion rates similar to those obtained in laying hens fed diet with the nutritional level recommended for the breed. However, protease supplementation did not show effect on egg shell quality.